Ngoara Tei Social Institution Model in Grounding Islamic Education Based on Local Wisdom of the Bima Community - Abd Salam (FiTUA: JURNAL STUDI ISLAM, 2026)
Social institutions based wisdom local own role important in internalize values Islamic education, however studies that position it as an educational model based public Still limited. Research This aim analyze institutions social Ngoara Tei as a grounding medium Islamic education based on wisdom local Bima society and formulate a conceptual model that explains mechanism internalization Islamic values through culture local. Research use approach qualitative with type study library research. Data obtained from article scientific reputable, books academic and literature relevant, then analyzed use content analysis through stages data condensation, data presentation, and retrieval conclusion. Research results show that Ngoara Tei transform values Islamic education through mutual cooperation, deliberation , role models, participation social, habituation, and experience Culture. The values of trust, brotherhood, mutual assistance, charity, courtesy, and good manners internalized so that form character religious, social, moral, and humanistic. Research novelty This is the Ngoara Tei Social Institution Model which integrates culture local as input, Islamic values as core values, social processes as mechanism internalization, Islamic character as output, and Islamic education based on wisdom local as outcome. This model expand paradigm Islamic education based on contextual, adaptive, and sustainable society.